Pathology of non-alcoholic fatty liver disease - Cataldo, Ivana (Pathologica, 2021)
Non-alcoholic fatty liver disease (NAFLD) encompasses a spectrum of different conditions which are characterized by hepatic steatosis in the absence of secondary causes. It is currently the most common chronic liver disease worldwide, and its estimated prevalence is about 1.5-6.5%. The only histological finding of steatosis (“simple” steatosis) represents the uncomplicated form of NAFLD, while non-alcoholic steatohepatitis (NASH) is its inflammatory subtype associated with disease progression to cirrhosis and hepatocellular carcinoma (HCC), and represents the major indication for liver transplantation. NASH is still a diagnostic and therapeutic challenge for clinicians and liver biopsy is currently the only accepted method to reliably distinguish NASH from “simple” steatosis. From the histological perspectives, NAFLD and NASH continue to be an area of active interest for pathologists, with a specific focus on better methods of evaluation, morphologic clues to pathogenesis, and predictors of fibrosis progression. This review focuses on histopathology of NAFLD in adults, with the aim to provide a practical diagnostic approach useful in the clinical routine.